Apakah Gender Bermakna Pada Model Pembentukan Minat Berwirausaha? - Andhy Setyawan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
This research purposes to examine the moderating role of gender on the entrepreneurial intention model. The Theory of the Entrepreneurial Event (TEE) and Theory of Planned Behavior (TPB) are integrated as grand theory to explain the research. The data were obtained by involving 154 active undergraduate students as respondents. The results from Structural Equation Modeling (SEM) analysis approach showed that gender moderate the direct effect of entrepreneurial knowledge on entrepreneurial intention significantly. The positive effect of entrepreneurial subjective norm on entrepreneurial intention is stronger and significant in female respondents than males. Furthermore, the effect of the perceived feasibility on entrepreneurial intention is not moderated by gender.